iPod, YouTube, Wii play : theological engagements with entertainment - Laytham, D. Brent (Eugene, Or. : Cascade Books, 2012)
"Should Christians w00t or wail about the scope and power of modern entertainment? Maybe both. But first, Christians should think theologically about our human passion to be enteprtained as it relates to the popular culture that entertains us. Avoiding the one-size-fits-all celebrations and condemnations that characterize the current fad of pop culture analyses, this book engages entertainments case by case, uncovering the imaginative patterns and shaping power of our amusements. Individual chapters weave together analyses of entertainment forms, formats, technologies, trends, contents, and audiences to display entertainment as a multifaceted formational ecology."--Publisher's website.
Now that's entertainment -- No via media between superpowers and trivial pursuits -- iPod : our song gone wrong? -- YouTube and U2charist : community, convergence, and communion -- The trouble with Twitter -- We play -- We watch them play (sports) -- Gambling doesn p(l)ay -- Wii play : videogames -- CosmoGirl as cheap grace -- What would Bono do? -- The church of Oprah? -- Love cinema, hate the sin?
Includes bibliographical references (p. 197-203) and index.
Keywords: Religion and culture; Theology; Mass media and culture; Popular culture -- Religious aspects; Mass media -- Religious aspects; Popular culture -- United States; Video games -- Religious aspects -- Christianity; Christianity and culture; Christian ethics; Mass media -- Social aspects; Mass media -- Moral and ethical aspects; Mass media -- Religious aspects -- Christianity; Communication; Online social networks